The responsibility of the construction manager for the construction site safety - Czopek, Michał (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
In this article the author have presented Polish construction accident statistics, described a construction manager function and the Polish regulations (Building code, Labour code, Civil Code) which determine the manager’s responsibilities in the case of negligence that could have a negative effect on people’s health and lives. The example of accident and penalties for a construction manager in respect of professional liability were shown. In conclusion the role of building diary as documentary evidence in the disciplinary proceedings against the construction manager was described. There was also presented the examples of good practice in the accident occurrence situations analysis.